Analysis of programs for calculation of the system characteristics of ultra-wide range receiving paths - D. V. Arkhipenkov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2021)
When designing radio engineering products, at the early stages,one of the most important tasks to be solved is to determine the effective version of the system/device by analyzing all possible available versions. Therefore, the development of such systems / devices is a complex and time-consuming process, which involves an infinitely large number of iterations of calculations and simulations of various options in search of an optimal and  efficient  one.  This  article  describes  the  programs:  AppCAD from  Agilent  and  ADISimRF  from  Analog Devices. These programs have a large functionality, a lot of calculated system characteristics of the path, but each of them has shortcomings, for example, the lack of an editable database of integrated circuits (IC), the lack of dynamic range calculations for third-order intermodulation of the receiving path, theinability to optimize for nonlinear  distortions,  etc.The  purpose  of  the  article  is  to  develop  an  original  program  for  calculating  radio receiving  paths,  which  is  not  inferior  in  functionality  to  foreign  analogues  and  has  a  number  of  useful refinements for calculations. The article presents formulas forcalculating the noise figure of an analog-to-digital converter (ADC) and makes a comparative analysis of the resultsobtained with the real value. The noise figure of the radio receiving path is refined by including the reverseloss coefficient and the ADC noise figure in the formula. The program developed by the author of the article hasan editable element base, which simplifies and accelerates the calculation of the device. The algorithm of theprogram developed by the author is described, and the calculation of the system characteristics of the path for comparison with foreign analogues is given.